Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1002/1521-4141(200003)30:3<931::aid-immu931>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Protection of T cells from activation-induced cell death by Fas+ B cells

Abstract: Naive CD4+ T cells proliferate strongly in response to stimulation by superantigens such as staphylococcal enterotoxin B (SEB). However, when these same cells revert to a resting phenotype and are subjected to restimulation with either SEB or anti‐CD3, the majority of these SEB‐responsive cells undergo Fas ligand (FasL)‐mediated activation‐induced cell death (AICD). We investigated the impact of Fas expression on T cell AICD by utilizing B cell stimulators that lacked functional FasL and either expressed or di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
0
7
1
Order By: Relevance
“…Collectively, these findings suggest that like activated dendritic cells, activated B cells trigger the apoptosis of diabetogenic T cells in vivo, contributing to the therapeutic action of activated B cells. However, our observations contrast with recent findings that B cells activated through the engagement of CD40 and IgM can protect activated T cells from AICD in vitro (18). These contrasting observations may stem from the different agents used to activate the B cells.…”
Section: Cd25contrasting
confidence: 99%
See 1 more Smart Citation
“…Collectively, these findings suggest that like activated dendritic cells, activated B cells trigger the apoptosis of diabetogenic T cells in vivo, contributing to the therapeutic action of activated B cells. However, our observations contrast with recent findings that B cells activated through the engagement of CD40 and IgM can protect activated T cells from AICD in vitro (18). These contrasting observations may stem from the different agents used to activate the B cells.…”
Section: Cd25contrasting
confidence: 99%
“…Recent studies have demonstrated that B cells are crucial APCs in the pathogenic T cell response to glutamic acid decarboxylase (GAD) and for overcoming a checkpoint in T cell tolerance to ␤ cell Ags (16,17). Furthermore, B cells activated by engaging CD40 and IgM can rescue activated T cells from activation-induced cell death (AICD) (18). Therefore, administering activated B cells to prediabetic NOD mice may promote ␤ cell-reactive T cell responses and exacerbate the disease process.…”
mentioning
confidence: 99%
“…In keeping with this, Fas resistant B cells are better APCs than Fas-sensitive B cells (16). Furthermore, Fas-resistant B cells block activation-induced cell death within the T cell pool (17). These latter results suggest that Fas resistance may not only enhance B cell responses, but may promote and prolong T cell responses as well.…”
mentioning
confidence: 55%
“…Our results indicated that this protective signal did not affect CTL activation, cytokine secretion or cytolytic activity. One published report indicates that Fas ϩ B cells are able to protect T cells from AICD by redirecting FasL expression on T cells away from those T cells (52). It was a distinct possibility that the Th cells were acting through a similar mechanism to protect CTL.…”
Section: Discussionmentioning
confidence: 99%